2012
DOI: 10.1021/mp200287c
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles for Increasing the Oral Bioavailability and Permeation of Poorly Water Soluble Drugs

Abstract: We investigate the effects of spherical mesoporous silica nanoparticles (MSNs) as an oral drug delivery system to improve the oral bioavailability of the model drug telmisartan (TEL) and examine their cellular uptake and cytotoxicity. Further, we explore the mechanisms behind the improved oral absorption of poorly soluble drugs promoted by MSNs. An investigation of intestinal epithelial cellular binding, association and uptake was carried out by laser scanning confocal microscopy, transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(91 citation statements)
references
References 43 publications
4
87
0
Order By: Relevance
“…There are a few studies demonstrating increased drug bioavailability and/or permeability for drug-loaded MSN formulations after oral administration [48][49][50][51] relying on the enhanced solubility that can be attained for poorly soluble drugs upon loading into a porous matrix with subsequent release into the GI tract. 52,53 To our knowledge, however, the present study is the first to demonstrate the potential of intestinal targeting of the MSN drug delivery carrier itself, with subsequent cellular uptake and intracellular release of a poorly soluble drug important for clinical use.…”
Section: Functionalized Msns Can Be Internalized By Intestinal Epithementioning
confidence: 99%
“…There are a few studies demonstrating increased drug bioavailability and/or permeability for drug-loaded MSN formulations after oral administration [48][49][50][51] relying on the enhanced solubility that can be attained for poorly soluble drugs upon loading into a porous matrix with subsequent release into the GI tract. 52,53 To our knowledge, however, the present study is the first to demonstrate the potential of intestinal targeting of the MSN drug delivery carrier itself, with subsequent cellular uptake and intracellular release of a poorly soluble drug important for clinical use.…”
Section: Functionalized Msns Can Be Internalized By Intestinal Epithementioning
confidence: 99%
“…Mesoporous silica nanoparticles are considered to be very promising candidate for drug delivery specifically for water-insoluble drug. Due to large surface areas and pores, these MSNPs act as reservoirs for storing hydrophobic drugs, whereas their shape and size can be altered according to the requirements (Zhang et al 2012;Bharti et al 2015). Several drugs with low water solubility have been explored to demonstrate this concept including ibuprofen, rifampin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…26 A large number of silica-based pharmaceutical studies have been reported, including controlled and targeted drug delivery, even at the subcellular level. [27][28][29] In contrast to most of the other reports in this field, Dessivio et al 15 proposed a hybrid strategy to take advantage of both silica and organic systems. The constructed silica-coated liposomes, called "Liposil," possessed the high stability of silica materials and versatile drug-loading capabilities of liposomes, providing a novel potential carrier for drug delivery, especially in hostile bioenvironments.…”
Section: Results and Discussion Preparation And Characterization Of Cmentioning
confidence: 99%